Direct Measurements of the Malvinas Current Velocity Structure - Frey, D. I. (2021)
Direct velocity measurements of the Malvinas Current (MC) were carried out on multiple occupations of five transects across the flow using a Shipborne Acoustic Current Profiler (SADCP) on the R/V Akademik Sergey Vavilov and Akademik Mstislav Keldysh. These data are used to determine local features of the three-dimensional velocity field of the current. The occupations covered the northern branch of the Antarctic Circumpolar Current (ACC) and the southern part of the MC. Five transects across the flow were located at 350–550 km from each other from the Drake Passage to the western Argentine Basin at 46°S. The new observations reveal that the current is organized in two branches, namely, an inshore branch extending to a depth of 200–300 m and a main offshore branch, which flows approximately over the 1,400 m isobath. This two-branch structure is observed on each of the cross-flow transects. The observed velocities of the inshore branch exceed 40 cm/s on each studied crossing of the current. The MC is a cold western boundary current that follows the Subantarctic Front. This flow originates as an offshoot of the northern branch of the ACC and continues over the Falkland/Malvinas Plateau and along the western slope of the Argentine Basin. Volume transports of the upper 700 m of the MC calculated for each crossing range between 1.4 and 4.4 Sv for the inshore branch and between 21.2 and 25.5 Sv for the offshore (main) branch.